On Expression Patterns and Developmental Origin of Human Brain Regions - Kirsch, Lior; Chechik, Gal (PLOS Computational Biology, 2016)
Author Summary Genome-wide measurements of gene expression across the human brain can reveal new principles of brain organization and function. To achieve this, we aim to discover which genes are differentially expressed and in what brain regions. We found that almost all genes in the adult human brain bear a developmental ‘footprint’ which determines their areal expression-pattern based on the developmental ontology of brain regions, while at the same time their spatial expression pattern changes during life. Furthermore, pairs of paralog genes and similar genes with stronger embryonic footprint, tend to be more strongly correlated (or anti correlated) suggesting that their expression is more strongly spatially tuned, and this tuning changes in development.